2017
DOI: 10.1039/c6ra27840j
|View full text |Cite
|
Sign up to set email alerts
|

Towards high visible light photocatalytic activity in rare earth and N co-doped SrTiO3: a first principles evaluation and prediction

Abstract: The band structure and photocatalytic activity of RE (La, Ce, Pr or Nd) mono-doped and RE–N co-doped SrTiO3 for band gap reduction are studied systematically using first principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…Figure 2 depicts the UV-Vis DRS spectra (Figure 2a-c) and the optical band gap energy (Eg) (Figure 2d) of the SrTiO 3 , SrTiO 3 :Ru and SrTiO 3 :RuO 2 :NiO samples, where it is possible to verify that: (i) the pristine SrTiO 3 presented a characteristic absorption band in the UV light region and the highest Eg value of ca. 3.2 eV (estimated through the application of Kubelka-Munk method [24]) in accordance with the literature [25], with an absorption edge around 380-390 nm, corroborating the need towards a spectral red-shift; (ii) the decoration of the SrTiO 3 with Ru nanoparticles indeed increased the response against the visible irradiation since the Eg values decreased by about 8-14%, compared to SrTiO 3 , resulting in a wide absorption band between 400-800 nm due to the RuO 2 plasmon band, as also recorded Mateo et al [21]; (iii) the impregnation with nickel further increased the visible light harvest, mainly after 520 nm through the ion transition level [26], and narrowed the Eg between 14-20%, compared to SrTiO 3 ; (iv) the global spectrum intensity progressively increased as the dopant concentration raised; (v) the Eg values did not follow a gradual decay pattern as the metal oxides' concentration increase, since the presence of excessive ions can induce intrinsic point defects, or oxygen vacancies, on the surface of metal-doped semiconductors, which may act as recombination centers [27,28]; and (vi) the double doping approach led to a partial suppression of the higher energy ions, resulting in a photocatalyst with weaker UV light absorption between 200-400 nm, when compared to Ru-doped SrTiO 3 , as similarly reported for the co-doping of SrTiO 3 with Ni and Ta/La [17,20,29].…”
Section: Characterization Of the Photocatalystssupporting
confidence: 68%
“…Figure 2 depicts the UV-Vis DRS spectra (Figure 2a-c) and the optical band gap energy (Eg) (Figure 2d) of the SrTiO 3 , SrTiO 3 :Ru and SrTiO 3 :RuO 2 :NiO samples, where it is possible to verify that: (i) the pristine SrTiO 3 presented a characteristic absorption band in the UV light region and the highest Eg value of ca. 3.2 eV (estimated through the application of Kubelka-Munk method [24]) in accordance with the literature [25], with an absorption edge around 380-390 nm, corroborating the need towards a spectral red-shift; (ii) the decoration of the SrTiO 3 with Ru nanoparticles indeed increased the response against the visible irradiation since the Eg values decreased by about 8-14%, compared to SrTiO 3 , resulting in a wide absorption band between 400-800 nm due to the RuO 2 plasmon band, as also recorded Mateo et al [21]; (iii) the impregnation with nickel further increased the visible light harvest, mainly after 520 nm through the ion transition level [26], and narrowed the Eg between 14-20%, compared to SrTiO 3 ; (iv) the global spectrum intensity progressively increased as the dopant concentration raised; (v) the Eg values did not follow a gradual decay pattern as the metal oxides' concentration increase, since the presence of excessive ions can induce intrinsic point defects, or oxygen vacancies, on the surface of metal-doped semiconductors, which may act as recombination centers [27,28]; and (vi) the double doping approach led to a partial suppression of the higher energy ions, resulting in a photocatalyst with weaker UV light absorption between 200-400 nm, when compared to Ru-doped SrTiO 3 , as similarly reported for the co-doping of SrTiO 3 with Ni and Ta/La [17,20,29].…”
Section: Characterization Of the Photocatalystssupporting
confidence: 68%
“…Unfortunately, these localized 3 d states of magnetic impurities would induce the photo‐generated carriers recombination centers thus decrease the photocatalytic efficiency . The previous experiments and theories have been found that the synergistic effect of cationic‐anions co‐doping could overcoming the negative effect of the cationic mono‐doping . Among all the anionic dopants, N‐doped STO is one successful example to extending the absorption edge to visible light, which is mainly due to a p ‐type doping character after one N atom substituting at a O site .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, (V/Nb/Ta, N) [36], (Sb, N) [37], (Mo/W, 2N) [38], (La/Ce/Pr/Nd, N) [39], and (Rh, 2F) [40] codoping has been studied, the latter turning out to be appropriate for water splitting. Cation-cation codoping has been addressed experimentally for (Ag, Nb) [41] and (La, Cr) [42], showing that visible light absorption is not possible, and theoretically for (Na/K/V/Nb/Ta, Rh) [36] and (La, Rh) [43], finding that (Rh, V) codoping is advantageous for water splitting.…”
Section: Introductionmentioning
confidence: 99%